PENDAMPINGAN KADER JOYOBOYO DALAM DETEKSI DINI KESEHATAN JIWA DI MASYARAKAT - Rinawati, Fajar; Bambang Wiseno; Dwi Rahayu; Didik Susetiyanto Atmojo; Elfi Quyumi Rahmawati (Universitas Kadiri, 2023)
Mental health problems that occur in the community are currently not detected early, so that mental disorders are only handled when they become chronic. The purpose of this activity is to provide knowledge and skills on how to detect mental health in the community. This activity was carried out in the Kaliombo Village with 33 participants. The training activities provided began with providing knowledge about mental health in general, the characteristics of mental health, risks and mental disorders, as well as theories about how to detect early. then examples are given, and participants practice early detection methods. After that, an evaluation was carried out, in which each participant tried to detect early his friend who was accompanied by a facilitator. Joyoboyo cadres really need to be provided with provision regarding early detection of mental health, so that mental health problems will be detected and handled promptly and appropriately.